2020
DOI: 10.1021/acs.jafc.0c04500
|View full text |Cite
|
Sign up to set email alerts
|

Glucuronidation of Methylated Quercetin Derivatives: Chemical and Biochemical Approaches

Abstract: Botanical supplements derived from grapes are functional in animal model systems for the amelioration of neurological conditions, including cognitive impairment. Rats fed with grape extracts accumulate 3′-O-methyl-quercetin-3-O-β-d-glucuronide (3) in their brains, suggesting 3 as a potential therapeutic agent. To develop methods for the synthesis of 3 and the related 4′-O-methyl-quercetin-7-O-β-d-glucuronide (4), 3-O-methyl-quercetin-3′-O-β-d-glucuronide (5), and 4′-O-methyl-quercetin-3′-O-β-d-glucuronide (6),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Due to its abundance in many plants the majority of formulations obtain glycosides of flavonoids from natural sources, with production of flavonoids from plants being investigated extensively and external growing conditions optimised to improve yields, however in vitro formation is possible and has been achieved both chemically and biosynthetically. 190–193 Successful efforts into the formation of quercetin by cell cultures have also been achieved. 194…”
Section: Anti-ageing Ingredientsmentioning
confidence: 99%
“…Due to its abundance in many plants the majority of formulations obtain glycosides of flavonoids from natural sources, with production of flavonoids from plants being investigated extensively and external growing conditions optimised to improve yields, however in vitro formation is possible and has been achieved both chemically and biosynthetically. 190–193 Successful efforts into the formation of quercetin by cell cultures have also been achieved. 194…”
Section: Anti-ageing Ingredientsmentioning
confidence: 99%
“…Glucuronidation is typically a phase II metabolic process, considered a detoxification step in the mammalian system ( Stachulski and Meng, 2013 ). However, glucuronide metabolites often possess enhanced water solubility and polarity compared to their corresponding aglycones, indicating their potent pharmacological activities ( Docampo-Palacios et al, 2020 ). For instance, morphine-6-O-glucuronide demonstrates a 100-fold stronger anesthetic effect than morphine, as evidenced by clinical trials ( Kilpatrick and Smith, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…3′-methyl-quercetin-3-glucuronide, quercetin-3-glucuronide, and quercetin-3’-sulfate have been identified as major plasma metabolites after 1.5 h from the consumption of fried onions [ 30 , 32 ]. These quercetin metabolites are formed in the small intestine and liver by biotransformation enzymes including UDP-glucuronyltransferases as a result of phase II metabolism [ 29 , 39 , 40 ]. It was also reported that conjugated metabolites of quercetin accumulate in human plasma in the concentration range of 10 −7 to 10 −6 M after the periodic ingestion of onions with meals for 1 week [ 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since these compounds have been observed as the main forms of conjugated quercetin metabolites, studies focusing on the biological activity of flavonols using these conjugated metabolites would be essential, which prompted us to study the biological activity of one of the conjugated quercetin metabolites. One of the most abundant glucuronide metabolites found mainly in plasma and tissues including the liver, kidney, and brain is quercetin 3-O-β-D-glucuronide (Q-3-G) ( Figure 1 ) [ 31 , 35 , 40 , 42 , 43 ], which may generate similar, stronger, or weaker activities compared with parent compounds in different models. Q-3-G is transported to target tissues via plasma to exert its biological activity [ 39 ].…”
Section: Introductionmentioning
confidence: 99%